2-(Tritylsulfanyl)ethyl 2-iodobenzoate - Zhu, Xin; Lu, Ping; Ng, Seik Weng (International Union of Crystallography, 2011)
The methine C atom of the triphenylmethyl group in the title compound, C 28H 23IO 2S, is slightly flattened out [∑Cphenyl - C - Cphenyl = 335.6 (5)°]. The -C - O - C - C - S- chain connecting the triphenylmethyl group and the aromatic ring adopts an extended zigzag conformation, these five atoms lying on an approximate plane (r.m.s. deviation = 0.120 Å).